2016
DOI: 10.1128/jvi.03248-15
|View full text |Cite|
|
Sign up to set email alerts
|

Deep Sequencing Reveals Potential Antigenic Variants at Low Frequencies in Influenza A Virus-Infected Humans

Abstract: Influenza vaccines must be frequently reformulated to account for antigenic changes in the viral envelope protein, hemagglutinin (HA). The rapid evolution of influenza virus under immune pressure is likely enhanced by the virus's genetic diversity within a host, although antigenic change has rarely been investigated on the level of individual infected humans. We used deep sequencing to characterize the between-and within-host genetic diversity of influenza viruses in a cohort of patients that included individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
124
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(146 citation statements)
references
References 49 publications
20
124
1
1
Order By: Relevance
“…For instance, one recent study deep-sequenced HA from several hundred patients but only found a small number of antigenic variants, and mostly at low frequencies (Dinis et al, 2016). But our study suggests that influenza may experience many of the same selective pressures within acute infections as it does globally, even if the short durations of these infections make it difficult for selected mutations to reach frequencies that are detectable with current methods.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one recent study deep-sequenced HA from several hundred patients but only found a small number of antigenic variants, and mostly at low frequencies (Dinis et al, 2016). But our study suggests that influenza may experience many of the same selective pressures within acute infections as it does globally, even if the short durations of these infections make it difficult for selected mutations to reach frequencies that are detectable with current methods.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical significance achievable in these studies is limited by the number of animal pairs that can be examined [67][68][69]. Furthermore, the comparison between one genotype and another may be confounded by viral heterogeneity, whereby each population contains a cloud of genetic diversity [24,70]. As we have shown, data from replicate transmission events leads to an improved ability to infer selection, in particular by reducing the false positive rate of inference and by increasing the accuracy in inferred selection coefficients.…”
Section: Inferring Parameters Of Transmission From Viral Sequence Datamentioning
confidence: 99%
“…Influenza evolution at a population level has been studied years, yet, new antigenic variants are initially generated and selected at the level of the individual infected host. Within a host, influenza viruses exist as a "swarm" of genetically distinct viruses [41]. Sanger sequencing defines consensus sequences and cannot resolve minority variants below 20% of the viral population.…”
Section: Viral Evolutionmentioning
confidence: 99%
“…Deep sequencing has been used in natural infection and human challenge studies to characterize between and within host genetic diversity [41,42]. The identification of low frequency mutations in the hemagglutinin (HA) antigenic sites or near the receptor-binding domain in vaccinated and unvaccinated influenza infected persons highlight viral evolution within a host due to selective immune pressure [41]. Similarly, NGS can reveal the rapid evolution of drug resistant variants during therapy [43].…”
Section: Viral Evolutionmentioning
confidence: 99%